Disability pension due to common mental disorders and subsequent suicidal behaviour: a population-based prospective cohort study. Issue 4 (4th April 2016) - Rahman, Syed Ghulam; Alexanderson, Kristina; Jokinen, Jussi; Mittendorfer-Rutz, Ellenor
Abstract : Objective: Adverse health outcomes, including suicide, in individuals on disability pension (DP) due to mental diagnoses have been reported. However, scientific knowledge on possible risk factors for suicidal behaviour (suicide attempt and suicide) in this group, such as age, gender, underlying DP diagnoses, comorbidity and DP duration and grade, is surprisingly sparse. This study aimed to investigate associations of different measures (main and secondary diagnoses, duration and grade) of DP due to common mental disorders (CMD) with subsequent suicidal behaviour, considering gender and age differences. Design: Population-based prospective cohort study based on Swedish nationwide registers. Methods: A cohort of 46 515 individuals aged 19–64 years on DP due to CMD throughout 2005 was followed-up for 5 years. In relation to different measures of DP, univariate and multivariate HRs and 95% CIs for suicidal behaviour were estimated by Cox regression. All analyses were stratified by gender and age. Results: During 2006–2010, 1036 (2.2%) individuals attempted and 207 (0.5%) completed suicide. Multivariate analyses showed that a main DP diagnosis of 'stress-related mental disorders' was associated with a lower risk of subsequent suicidal behaviour than 'depressive disorders' (HR range 0.4–0.7). Substance abuse or personality disorders as a secondary DP diagnosis predicted suicide attempt in all subgroups (HR range 1.4–2.3) and suicide in women and younger individuals (HR range 2.6–3.3). Full-time DP was associated with a higher risk of suicide attempt compared with part-time DP in women and both age groups (HR range 1.4–1.7). Conclusions: Depressive disorders as the main DP diagnosis and substance abuse or personality disorders as the secondary DP diagnosis were risk markers for subsequent suicidal behaviour in individuals on DP due to CMD. Particular attention should be paid to younger individuals on DP due to anxiety disorders because of the higher suicide risk.